Topical Antioxidant Potential of Telang Flower Extract (Clitoria ternatea L.) on IL-6 and VEGF Regulation in UV-B Exposure: An In Vivo Experimental Study - Retno Adaninggar; Titiek Sumarawati; Chodidjah (Gema Lingkungan Kesehatan, 2025)
UVB radiation can penetrate the epidermis and can induce DNA damage in skin cells by increasing ROS concentrations. Apart from that, UVB radiation also increases melanocyte proliferation which can cause melasma. Skin damage due to UV exposure is caused by the generation of  ROS and various inflammatory factors. Telang flowers contain Glutathione, which is one of the main antioxidants in the body, which has a skin depigmentation function. One of the physiological effects of glutathione is to inhibit melanogenesis by suppressing tyrosinase activity. Experimental research with post test control group. Groups KN, P1 and P2 were each exposed to UVB at 302 nm with a MED of 160 mJ/cm2, while group K0 was a healthy group. P1 was given 5% butterfly pea flower gel and P2 was given 10% gel every day for 14 days, while KN received base gel. On the 21st day, the tissue was analyzed for IL-6 and VEGF level using ELISA. There was a significant difference in the mean levels of IL-6 between the four groups, with the One Way Anova test p = 0.000 (p <0.05). IL-6 levels decreased with increasing doses (P1=32.49±1.02, K4=27.82 ± 0.74) compared to the control (KN=61.89 ± 0.69, while K0=25.30 ± 0.55). Furthermore, the mean VEGF levels also had a significant difference between the four groups with the Kruskal Wallis test p = 0.000 (p <0.05) VEGF levels in the control group (KN = 37.44 ± 2.43) and followed by the healthy group (K0 = 23.47 ± 0.99), then in the P1 treatment group (K3 = 30.96 ± 0.57) were higher than the P2 treatment group (K4 = 27.00 ± 1.55). Administration of butterfly pea flower gel can reduce the level of the IL-6 gene and increase the level of the VEGF gene in the skin tissue of mice models of UVB light-induced hyperpigmentation.